PENGARUH PEMILIHAN UMUM (PEMILU) TAHUN 2009, 2014, DAN 2019 TERHADAP PASAR MODAL INDONESIA - Louisa Gabe Samosir; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2019)
This study aims to examine the impacts of political events, such a presidential election towards the Indonesian capital market in the last three periods of election, in 2009, 2014, and 2019. Samples used were the companies listed in LQ-45 from February to July for each period of election, in 2009, 2014, and 2019. This research took abnormal return and trading volume activity to be examined, thus used event study as the research model. The result shows there were no differences in abnormal return and trading volume activity, both before and after the elections in 2009, 2014, and 2019.